Organizational Schemes of Information Resources in Top 50 Academic Business Library Websites - Kim, Soojung; DeCoster, Elizabeth (The Journal of academic librarianship, 2011)
This paper analyzes the organizational schemes of information resources found in top 50 academic business library websites through content analysis and discusses the development and evaluation of the identified schemes.